La dinámica del comercio exterior venezolano (Siglo XIX) - Catalina Banko (Centre de Recherches sur les Mondes Américains, 2016)
The study of commercial networks between Venezuela and the ports of Europe and the United States is the central objective of this paper. For this purpose it is necessary to analyze the leading role played by commercial houses in terms of the articulation of trade flows and its connection with foreign markets and within regional areas. The research involves the study of the activities carried out by the German commercial firms, which not only control the traffic with Hamburg and Bremen but also with Liverpool, and even at the end of the century, expand their networks to ports located in the United States. In this context, Maracaibo became the biggest exporter of coffee in Venezuela. Puerto Cabello, which has a large hinterland that unfolds to the west-center and the plains region, remained in a second place, while La Guaira, who had held the lead in exports since colonial times, is displaced to a third position, even if it remains the foremost importer port in the country thanks to its proximity to Caracas, the capital of the Republic.